Clinical Study on the Effect of Simvastatin on Paraoxonase Activity - Muačević, Diana Katanec; Bradamante, Vlasta; Poljičanin, Tamara; Reiner, Željko; Babić, Zdravko; Simeon-Rudolf, Vera; Katanec, Davor (Arzneimittelforschung, 2007)
Human paraoxonase (PON1) is a serum high-density lipoprotein-associated phos-photriesterase. High-density lipoprotein (HDL) plays the role of a carrier and the site of action of this enzyme. According to a majority of authors, PON1 acts as an antioxidant, preventing low-density lipo-protein (LDL) peroxidation. However, due to the fact that in vivo serum PON1 is predominantly associated with HDL, its major physiological role might be to protect HDL, rather than LDL, from oxidation. Nevertheless, the physiological substrate of PON1 still remains to be discovered. The objective of this study was to determine changes in PON1 activity during treatment with simvastatin (CAS 79902-63-9, Lipex®) in patients with type IIa and/or IIb hyperlipoproteinemia. PON1 activity was assessed in 32 patients with hyperlipoproteinemia type IIa or IIb with an LDL cholesterol concentration higher than 4.2 mmol/l. Patients received simvastatin in a daily dose of 20 mg. The lipid status and PON1 activity were assessed at baseline, as well as 3 and 6 months after the beginning of treatment. The study demonstrated a statistically significant lipid lowering effect of simvas-tatin on total and LDL cholesterol, and an increase in PON1 activity in patients with both types of hyperlipoproteinemia. No statistically significant correlation was observed either between changes in PON1 activity and HDL, HDL2, HDL3 and LDL cholesterol and triglyceride levels, or between their first differences in patients with both type IIa and IIb hyperlipopro-teinemia . The obtained results suggest that the antioxidant properties of simvas-tatin might be caused by a mechanism independent of apoAI-containing lipopro-tein concentration. The antioxidant properties of simvastatin, which play an important role in HDL protection from oxidation, could be the mechanism inducing the increase in PON1 activity.
Keywords: Antioxidants; Aryldialkylphosphatase; CAS 79902-63-9; Cholesterol, high and low density lipoprotein; Lipex®; Paraoxonase; Simvastatin, clinical study, effect on paraoxonase activity